Regulatory roles of miRNAs in development and progression of Hepatocellular carcinoma - Yasmeen Ishaq; Bisma Rauff; Muhammad Rehan Chaudhry; Mohamad S. Hakim; Sana Khurshid; Shafiq Ahmad Chudhary; Aqsa Ikram (Molecular Biology Reports, 2026)

Facile synthesis of cobalt-iron layered double hydroxide and its derived mixed metal oxide for Congo red and Pb(II) remediation - Ramzan Akhtar; Adil Khan; Maria Gul; Mohsin Ali Raza Anjum; Iqra Rafique; Muhammad Rehan; Rashid Nazir Qureshi; Sajid Iqbal; Muhammad Saifullah (Colloids and Surfaces C: Environmental Aspects, 2026)

Pathogenic mechanisms of Aeromonas hydrophila and the protective role of probiotics in sustainable aquaculture - Gelana Urgesa Ayana; Mukhtar Muhammad Abdullateef; Gazahegn Wakjira Yadata; Rehan Manzoor; Sahr Lamin Sumana; Abate Melaku Gelata; Md Mohidul Islam (Archives of Microbiology, 2026)

Green mobility with battery electric buses: a review of transition and circularity integration - Syed Naveel Hussain; Kasun Hewage; Muhammad Zahid; Rehan Sadiq (Travel Behaviour and Society, 2026)

A metal-organic framework-based multifunctional film for active food preservation and visual spoilage monitoring - Muhammad Junaid Khan; Muhammad Rehan Islam; Farooq Hafeez; Yinyin Wang; Yunlei Xianyu (Chemical Engineering Journal, 2026)

Food waste derived biochar via pyrolysis: Properties, contaminant sequestration mechanisms, and environmental applications - Muhammad Waqas; Abdul-Sattar Nizami; Osman Atilla Arikan; Dilek Beyazli; Ali Temiz; Javed Nawab; Muhammad Naqvi; Mohammad Rehan (Environmental Research, 2026)

Adaptation of wild-type rabies virus on vaccine producing cell line and its quantification by peroxidase-based immunostaining - Muhammad Rehan Riaz; Syed Muhammad Kamran Ullah; Muhammad Rashid; Kaleem Ullah; Hamid Ahmad; Qari Muhammad Kaleem; Faiza Jamil; Saifullah Khan (Archives of Virology, 2026)

Multifunctional MXene film–embedded GFRP composites: Enabling EMI shielding and efficient electrothermal de-icing - Muhammad Yasir Khalid; Abdallah Kamal; Dawei Zhang; Lianxi Zheng; Kin Liao; Kamran Ahmed Khan; Rehan Umer (Chemical Engineering Journal, 2026)

The implication of continuous thermophilic composting for the resource recovery from slaughterhouse waste - Muhammad Waqas; Abdul-Sattar Nizami; Mohammad Rehan; Hesam Kamyab; Osman Atilla Arikan; Cosimo Magazzino (Biomass and Bioenergy, 2026)

Early winter precipitation variability over Pakistan and associated ENSO teleconnections - Romesa Najeeb; Irfan Ur Rashid; Rehan Ahmed; Muhammad Adnan Abid; Elham Ghasemifar; Ibrahim Alsafari (Theoretical and Applied Climatology, 2026)

Genome‐Guided Dissection of ser and shlB Uncovers Multifactorial Virulence Mechanisms of Serratia marcescens PXG6 in Plutella xylostella - Muhammad Rehan Akhtar; Jun Ma; Yan Sun; Xiaofeng Xia (Environmental Microbiology, 2026)
The rapid evolution of pesticide resistance in Plutella xylostella has reduced the effectiveness of conventional pest control methods in cruciferous crops. This study investigated the virulence of Serratia marcescens PXG6 against P. xylostella and identified two putative virulence factors, ser (serralysin) and shlB (hemolysin transporter). Whole‐genome sequencing revealed a GC content of 59.65%, 4650 predicted genes, multiple secretion systems (types I, V, and VI), and 715 putative virulence‐related genes. Bioinformatic analyses predicted type IV pili, serralysin, hemolysin, and flagella as pathogenic determinants. Purified prodigiosin exhibited concentration‐dependent insecticidal activity, whereas bacterial proteins alone caused little larval mortality, indicating that full virulence depends on live bacterial cells. Gene knockout mutants Δ ser and Δ shlB exhibited altered growth, motility, biofilm formation, and stress tolerance. Deletion of shlB significantly reduced hemolytic activity, protein secretion, and virulence against P. xylostella , whereas Δ ser had minimal impact on larval survival. Overall, PXG6 pathogenicity involves multiple bacterial components, with shlB playing a key role in virulence. These findings improve our understanding of the pathogenic mechanisms of PXG6 and support the development of S. marcescens ‐based biocontrol strategies against P. xylostella .

From concept to reality: current trends in developing tunable biopolymeric materials for food contact applications - Muhammad Rehan Khan; Elena Torrieri; Lorenzo Siroli; Francesca Patrignani; Florent Allais; Sami Fadlallah (Critical Reviews in Food Science and Nutrition, 2026)

Effects of urea-molasses-treated corn or rice straw silages as an alternative to corn silage in the diet of Sahiwal calves on growth performance, nutrient digestibility and economic benefits - Muhammad Iqbal Anjum; Muhammad Rehan; Shahbaz Javaid; Muhammad Mushahid (Tropical Animal Health and Production, 2026)

Engineering hybrid hydrogels from sticker–spacer peptide and molybdenum disulfide (MoS2) for advanced antimicrobial therapy - Muhammad Younis; Farhat Rafiq; Shuo Jin; Mussarat Tasleem; Muhammad Saleem; Yongchang Tian; Li Chen; Mohammad Aslam; Dalaver H. Anjum; Jabir Ubaid; Rehan Umer; Xiaofei Chen; et al. (Chemical Engineering Journal, 2026)

Pharmacological profiling of medicinal plants: a contemporary overview - Bilal Aslam; Muhammad Rehan Sajid; Asif Hussain; Ifraha Abbas (Natural Product Research, 2026)

Evaluation of Heavy Metal Contamination in Indus Deltaic Creeks Sediments, Sindh, Pakistan: Ecological Risk Assessment and Environmental Implications - Syed Muhammad Rehan Ullah; Syed Muhammad Saqib Nadeem; Sanober Kahkashan; Abdullah; Anwar Zeb (Marine Pollution Bulletin, 2026)

Sustainable valorization of leachate at Lakhodair landfill, Lahore: An integrated life cycle environmental and economic assessment of biogas production - Mehak Saghir; Aqsa Ayub; Abdul-Sattar Nizami; Mujtaba Baqar; Hesam Kamyab; Muhammad Waqas; Mohammad Rehan; Zaki-ul-Zaman Asam (Biomass and Bioenergy, 2026)

Solar-Driven Photocatalytic Degradation of Organic Pollutants by I-MnO₂/PTh Nanocomposite: Mechanisms, Kinetics, and Implications for Advanced Environmental Remediation - Muhammad Nayab; Ahmad Farhan; Muhammad Zahid; Zulfiqar Ahmad Rehan; Asim Jilani; Rafa Almeer; Hussameldin Ibrahim; Nabil Al-Zaqri (International Journal of Environmental Research, 2026)

Spherical fuzzy evidential reasoning for vehicle-to-grid enabled electric vehicle adoption: A data-driven analysis of public perception - Muhammad Zahid; Ezzeddin Bakhtavar; Salim Khoso; Syed Naveel Hussain; Rehan Sadiq; Kasun Hewage (Travel Behaviour and Society, 2026)

Multifunctional Mg-MOF-74@Carvacrol/Chitin nanofiber-based nanocomposite film for enhanced food packaging - Muhammad Junaid Khan; Muhammad Rehan Islam; Farooq Hafeez; Chunyan He; Jun Zhang; Yunlei Xianyu (Chemical Engineering Journal, 2026)

Anti-arthritic appraisal of Acorus calamus L. extracts in complete Freund’s adjuvant‑induced arthritic Wistar rats via regulating inflammatory cytokines and OPG/RANKL pathway - Muhammad Usman Bari; Asif Hussain; Bilal Aslam; Zia-ud-Din Sindhu; Muhammad Rehan Sajid; Rifat Ullah Khan (Inflammopharmacology, 2026)

Balancing efficacy and resistance: oils vs. synthetic acaricides in the control of Panonychus citri - Muhammad Asif Qayyoum; Syed Husne Mobarak; Bilal Saeed Khan; Rehan Inayat; Asad Nawab; Tian-Ci Yi (Experimental and Applied Acarology, 2026)

Recent advances in biochar-based materials for CO₂ capture: From preparation to application in value-added chemicals and fuels - Maroof Ali Panhwar; Boxi Geng; Bachirou Guene Lougou; Muhammad Rafique; Imran Ali; Rehan Khursheed; Akhil Garg; Yong Shuai (Journal of Environmental Chemical Engineering, 2025)

Optimizing hybrid insulation systems for diverse climates: A comparative analysis of composite material combinations in residential buildings - Salim Khoso; Ezzeddin Bakhtavar; Ahmed Abouyoussef; Muhammad Zahid; Kasun Hewage; Rehan Sadiq (Energy and Buildings, 2025)

Toxic Metals in the Workplace: Assessing Heavy Metal Contaminants in Indoor Dust of Auto Parts Stores and Their Impact on Health of Employees - Nadeem Ali; Sultan H. Alamri; Jahan Zeb; Mohammad Rehan; Nisreen Rajeh; Nabil Alhakamy; Mohamed I. Orif; Muhammad Imtiaz Rashid; Syed Ali Musstjab Akber Shah Eqani; Hani Z. Asfour (Water, Air, & Soil Pollution, 2025)

Microplastics in soil–plant systems: impacts on soil health, plant toxicity, and multiomics insights - Muhammad Ahsan Farooq; Fakhir Hannan; Hui-Xi Zou; Weijun Zhou; Dong-Sheng Zhao; Ahsan Ayyaz; Muhammad Asad Ullah Asad; Rehan Ahmad; Xiufeng Yan (Plant Cell Reports, 2025)

Cystic fibrosis in Pakistan: population harbouring rare variants non-responsive to CFTR modulators and the dilemma of poor health facilities - Anum Safdar; Muhammad Usman Ghani; Iqbal Bano; Tahir Mehmood; Hassan Rafique; Muhammad Farooq Sabar; Ali Akbar; Rehan Sadiq Shaikh (Molecular Biology Reports, 2025)

A survey-based study on knowledge, attitude, and perception of pet owners towards the use of plant extracts from bio-refinery in pet food formulations - Talal Hassan; Joana Nery; Mohammad Zaker Rehan; Muhammad Irfan Malik; Silvia Mioletti; Luigi Bertolotti; Alba Maria Ramos; Natascia Bruni; José M. Pinilla-Rosas; Maria Teresa Capucchio (Phytochemistry Letters, 2025)

Asiatic black bear in Pakistan: a comprehensive review and conservation indications - Faizan Ahmad; Muhammad Rehan; Luciano Bosso; Muhammad Kabir (Mammalian Biology, 2025)
The Asiatic black bear ( Ursus thibetanus ) is considered as globally vulnerable, and its distribution in Pakistan has drastically decreased. The current knowledge around its biology and ecology is still poor. To provide crucial management and conservation recommendations for this threatened bear in Pakistan and in other areas in the world, we examined all the literature published from 1977 to 2024 on the two subspecies of U. thibetanus living in Pakistan, i.e., the Baluchistan black bear ( U. thibetanus gedrosianus ) and Himalayan black bear ( U. thibetanus laniger ). We found 59 papers on the Asiatic black bear, with the majority of the studies focusing on the bears’ existence, distribution, and human-bear conflicts, while only one study used a genetic approach. Questionnaire/interview surveys emerged as the most used method, followed by sign surveys, camera trapping, and visual observations. Most of the publications were focused on the Himalayan black bear in Azad Jammu and Kashmir and the Mansehra district (northern Pakistan), while few studies have been conducted in Balochistan since 1977 for the subspecies Baluchistan black bear. This underscores a significant geographic gap in research, particularly in the southern Pakistan regions that host the threatened Baluchistan black bear. To address these gaps and improve conservation efforts, we recommend increasing applied research both inside and outside protected areas and employing updated methodologies like camera trapping, remote sensing, ecological modelling and genetic analysis. It is imperative to conduct studies across the entire distribution range, especially in understudied areas like southern Khyber Pakhtunkhwa and Balochistan, to ensure the long-term conservation of the Asiatic black bear across its entire distribution.

Polybenzimidazole-1D interconnected carbon framework decorated with nickel manganese oxide nanoparticles for hybrid supercapacitors - Muhammad Shahid Khan; Hong Meng; Ahmed Shuja; Hasan Ali; Hassan Tariq; Rehan Ullah; Abdullah Saad Alsubaie; Mohd Zahid Ansari; Yaqoob Khan; Imran Murtaza (Chemical Engineering Journal, 2025)

Comparative transcriptome and physiological analyses reveal involvement of photosynthesis, phytohormone signaling, and cysteine-methionine metabolism in arsenic toxicity tolerance in Brassica napus - Muhammad Ahsan Farooq; Fakhir Hannan; Hui-Xi Zou; Weijun Zhou; Dong-Sheng Zhao; Toqueer Abbas; Rehan Ahmad; Ahsan Ayyaz; Xiufeng Yan (Journal of Hazardous Materials, 2025)

Silver immobilized magnetic iron nanoparticles fabricated via green method for detection of cobalt in water and their antibacterial activity - Nasrullah Shah; Muffarih Shah; Khushboo Naz; Javariya Muhammad; Touseef Rehan; Asif Ali; Abbas Khan; Mohamed Bououdina; Muhammad Humayun (Environmental Science and Pollution Research, 2025)

Unmasking heavy metal contamination: Tracing, risk estimating and source fingerprinting from coastal sediments of the Payra River in Bangladesh - Salma Sultana; Niger Sultana; Mohammad Moniruzzaman; Muhammad Rehan Dastagir; Md Kamal Hossain (Marine Pollution Bulletin, 2025)

Characterization of meningitis-causing bacteria, with focus on genomic and pangenomic study of multi-drug resistant Streptococcus pneumoniae from cerebrospinal fluid - Rehan Ali; Kashif Ali; Muhammad Aurongzeb; Khalid Al-Regaiey; Junaid Ahmed Kori; Muhammad Irfan; Yasmeen Rashid; Danah Al Abduljabbar; Imdad Kaleem; Shahid Bashir (Antonie van Leeuwenhoek, 2025)

Improving green innovation performance: the role of integrating green customers and suppliers, government regulations, green knowledge integration capability - Sami Ullah; Tooba Ahmad; Muhammad Shafiq; Tariq Mehmood; Mohit Kukreti; Muhammad Rehan Shaukat (Environment, Development and Sustainability, 2024)

Advances in agar-based composites: A comprehensive review - Muffarih Shah; Abdul Hameed; Muhammad Kashif; Noor Majeed; Javariya Muhammad; Nasrullah Shah; Touseef Rehan; Abbas Khan; Jalal Uddin; Ajmal Khan; Hamdy Kashtoh (Carbohydrate Polymers, 2024)

Assessing the potential landslide risk identification in the northern section of CPEC route Pakistan based on Multi-Temporal InSAR approaches - Meer Muhammad Sajjad; Juanle Wang; Daqing Ge; Rehan Khan; Izhar Ahmed; Khan Zada (Journal of Mountain Science, 2024)

Role of quality assessment of the recycled packaging material in determining its safety profile as food contact material - Muhammad Rehan Khan; Muhammad Bilal Sadiq; Lukáš Vápenka; Stefania Volpe; Aleš Rajchl; Elena Torrieri (Waste Management, 2024)

Adaptive Event-Triggered Consensus Control of Nonlinear Multi-Agent Systems via Output Feedback Methodology: An Application to Energy Efficient Consensus of AUVs - Muhammad Arsal; Muhammad Rehan; Muhammad Khalid; Keum-Shik Hong (Journal of Marine Science and Engineering, 2024)
For dealing with the energy consumption in multi-agent systems (MASs), an event-triggered (ET) methodology is promising, which relies on the activation of communication devices only when communication of data is needed. This paper explores the leaderless consensus for nonlinear MASs using an adaptive ET approach via an output feedback methodology. This adaptive ET scheme is preferred as it can adapt to the environment through setting a communication threshold. The proposed approach renders the observed states of agents by use of nonlinear observers in an output feedback control dilemma, making it more practical. Simple Luenberger observers are developed to avoid the problem of always measuring agents’ states. The strategy of adaptive ET-based control is employed to minimize resource use and information transmission. Design conditions for the observer-based adaptive ET consensus control of nonlinear MASs have been derived via a Lyapunov function, containing state estimation error, consensus error, adaptation term, and nonlinearity bounds. In contrast to the existing methods, the present approach applies a more practical output feedback schema, uses adaptive ET proficiency, and deals with nonlinear agents. An example of a formation of autonomous underwater vehicles achieving the basic consensus realization between displacement and velocity is included to illustrate the viability of the resultant approach.

Evaluation of carob tree (Ceratonia siliqua L.) pods, through three different drying techniques, and ultrasonic assisted extraction, for presence of bioactives - Ashiq Hussain; Muhammad Rehan Arif; Adnan Ahmed; Salah Laaraj; Nida Firdous; Muhammad Qasim Ali; Haya Fatima; Shazia Yaqub; Samina Kauser; Rizwan Nisar; Faiza Iftikhar Gorsi; Ghulam Mueen Ud Din; et al. (South African Journal of Botany, 2024)

Co-production and enhancement of biogas and biohydrogen by optimizing NaOH-urera pretreatment conditions for kitchen waste - Asad A. Zaidi; Sohaib Z. Khan; Hamad Almohamadi; Mohammad Rehan; Muhammad Abdul Qyyum (Process Safety and Environmental Protection, 2024)

Regression-based prediction of flow-induced dominant vibrational frequencies in two-phase flow regimes - Muhammad Sohail; William Pao; Abdul Rahim Othman; Huzaifa Azam; Muhammad Rehan Khan (Ocean Engineering, 2024)

Drought variability in Pakistan: Navigating historical patterns in a changing climate with global teleconnections - Muhammad Latif; Hira Shireen; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi (Theoretical and Applied Climatology, 2024)

Correction to: Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Comparative influence of active PLA and PP films on the quality of minimally processed cherry tomatoes - Muhammad Rehan Khan; Lukas Vapenka; Muhammad Bilal Sadiq; Elena Torrieri; Ales Rajchl (Food Packaging and Shelf Life, 2024)

Application of species distribution models to estimate and manage the Asiatic black bear (Ursus thibetanus) habitat in the Hindu Kush Mountains, Pakistan - Muhammad Rehan; Ammar Hassan; Shah Zeb; Sami Ullah; Faizan Ahmad; Eve Bohnett; Luciano Bosso; Tosif Fida; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Assessing Asiatic black bear (Ursus thibetanus) temporal overlap and co-occurrence with sympatric species in the temperate zone of the Hindu Raj Mountain range - Faizan Ahmad; Muhammad Rehan; Eve Bohnett; Ammar Hassan; Sami Ullah; Shah Zeb; Hammad Ali Mian; Muhammad Kabir (European Journal of Wildlife Research, 2024)

Spatiotemporal analyses of temperature and equivalent temperature and their relationship with crop health across Pakistan’s cropland - Muhammad Latif; Momel Zoon; Shahzada Adnan; Rehan Ahmed; Abdelwaheb Hannachi; Rashed Mahmood; Muhammad Umar (Theoretical and Applied Climatology, 2024)

Spatiotemporal distribution and population trends of Sindh ibex (Capra aegagrus blythii) in Balochistan during 2019–2022 - Najeeb Ullah; Irum Basheer; Zhang Minghai; Muhammad Nawaz Rajpar; Muhammad Rehan; Muhammad Tayyab Khan (European Journal of Wildlife Research, 2024)
The increased pressures generated by human activities in form of climate change and habitat fragmentation have caused serious threats for Sindh ibex ( Capra aegagrus blythii ). Balochistan, recognized as one of the most vulnerable regions to climate change in Pakistan, has limited data on the distribution and population status of this species. To address this gap, our study aims to assess the spatial and temporal distribution and population trend of Sindh ibex in the Khuzdar and Lasbela districts of Balochistan. The study covered an area of approximately 45,123.97 km 2 . It involved a double-observer survey at ten sites from 2019 to 2022, using the BBRecapture package in the R programming language to estimate ibex population trend and dispersion. We provided a comprehensive update of the species geographic range, along with estimates of its current abundance and population trends. Over the course of four years, the ibex population fluctuated. The ibexes detected dropped from 720 (male to female ratio 1:1.21) and 710 (male to female ratio 1:1.08) in 2019 and 2020, respectively, to 550 (male to female ratio 1:1.35) and 548 (male to female ratio 1:1.09). Overall, this study provides valuable insights into the population trends, gender ratios, habitat preferences, and density of Sindh ibex in Balochistan over the four-year period. These findings contribute significantly to the baseline data on the species ecology and will further help in the conservation of these species at local scale.

Investigating the unparalleled effects of economic growth and high-quality economic development on energy insecurity in China: A provincial perspective - Jabbar Ul-Haq; Hubert Visas; Qazi Muhammad Adnan Hye; Raja Rehan; Sana Khanum (Environmental Science and Pollution Research, 2024)

Advancements in TiO2-based photocatalysis for environmental remediation: Strategies for enhancing visible-light-driven activity - Ruhma Rashid; Iqrash Shafiq; Muhammad Rehan Hasan Shah Gilani; Muhammad Maaz; Parveen Akhter; Murid Hussain; Kwang-Eun Jeong; Eilhann E. Kwon; Sungjun Bae; Young-Kwon Park (Chemosphere, 2024)

Nanoparticle elicitation: A promising strategy to modulate the production of bioactive compounds in hairy roots - Kamogelo M. Mmereke; Srividhya Venkataraman; Bertha Nametso Moiketsi; Muhammad Rehan Khan; Sayyeda Hira Hassan; Gaolathe Rantong; Kabo Masisi; Tebogo E. Kwape; Goabaone Gaobotse; Faisal Zulfiqar; Surender Kumar Sharma; Sonia Malik; et al. (Food Research International, 2024)

Green fabrication of copper nano-fertilizer for enhanced crop yield in cowpea cultivar: A sustainable approach - Muhammad Mustafa; Muhammad Azam; Haq Nawaz Bhatti; Amina Khan; Laiba Zafar; Abdul Malik Rehan Abbasi (Biocatalysis and Agricultural Biotechnology, 2024)

Nitric oxide reduces cadmium uptake in wheat (Triticum aestivum L.) by modulating growth, mineral uptake, yield attributes, and antioxidant profile - Muhammad Nawaz; Muhammad Hamza Saleem; Muhammad Rehan Khalid; Baber Ali; Shah Fahad (Environmental Science and Pollution Research, 2024)

Can synthetic biology really empower microbial biopolymers as efficient food contact materials? - Muhammad Rehan Khan; Elena Torrieri; Florent Allais; Sami Fadlallah (Trends in Food Science & Technology, 2024)

Impact of different proportions of sweet potato (Ipomoea batatas L.) flour on physical, chemical and sensory parameters of straight grade flour-based cake rusk - Hafiza Saher Rafique; Ashiq Hussain; Muhammad Nadeem; Abdul Rehman; Tahira Siddique; Ayesha Najam; Haseeb Haroon; Muhammad Rehan Arif; Shazia Yaqub; Haya Fatima; Salah Laaraj (Food and Humanity, 2023)

Physiological and Metabolic Changes in Maize Seedlings in Response to Bisphenol A Stress - Haziq Hussain; Rehan Naeem; Baharullah Khattak; Zia ur Rehman; Niamat Khan; Muhammad Kamran Qureshi; Farah Deeba; Iftikhar Ali; Muhammad Daud Khan (Journal of Soil Science and Plant Nutrition, 2023)

Interaction analysis of TRIM proteins and innate immunity mediators of common carp (Cyprinus carpio L.) to evaluate its affinity for ubiquitination and innate immune response - Muhammad Aizaz; Maryum Nisar; Rehan Zafar Paracha; Shijuan Shan; Nida Fatima Ali; Iqra Arshad; Guiwen Yang (Aquaculture, 2023)

Nanobiochar reduces ammonia emission, increases nutrient mineralization from vermicompost, and improves maize productivity - Muhammad Imtiaz Rashid; Ghulam Abbas Shah; Zahid Iqbal; Khurram Shahzad; Nadeem Ali; Mohammad Rehan; Nabil Abdulhafiz A. Alhakamy; Jiří Jaromír Klemeš (Journal of Cleaner Production, 2023)

Impact of gas composition and reservoir heterogeneity on miscible sour gas flooding — A simulation study - Madiyar Koyanbayev; Lei Wang; Yanwei Wang; Muhammad Rehan Hashmet; Randy D. Hazlett (Fuel, 2023)

The role of eco-innovation, renewable energy consumption, economic risks, globalization, and economic growth in achieving sustainable environment in emerging market economies - Qazi Muhammad Adnan Hye; Jabbar Ul-Haq; Hubert Visas; Raja Rehan (Environmental Science and Pollution Research, 2023)

Seismic risk assessment and hotspots prioritization: a developing country perspective - Rehan Asad; Muhammad Qaiser Saleem; Muhammad Salman Habib; Nadeem Ahmad Mufti; Shaker Mahmood Mayo (Natural Hazards, 2023)

The effects of trade, renewable energy, and financial development on consumption-based carbon emissions (comparative policy analysis for the G20 and European Union countries) - Muhammad Rehan; Selim Gungor; Mehjbeen Qamar; Aziza Naz (Environmental Science and Pollution Research, 2023)

Effect of ferulic acid derivative concentration on the release kinetics, antioxidant capacity, and thermal behaviour of different polymeric films - Muhammad Rehan Khan; Sami Fadlallah; Antoine Gallos; Amandine L. Flourat; Elena Torrieri; Florent Allais (Food Chemistry, 2023)

Valorization of organic biomass through the production of active biopolymer film based on sodium caseinate, guar gum, and beeswax - Mariavittoria Verrillo; Muhammad Rehan Khan; Stefania Volpe; Riccardo Spaccini; Elena Torrieri (Food Bioscience, 2023)

Exhumation History and Exploration Potential of Gold Deposits in the NE Jiaodong Peninsula, North China: Evidence from Apatite and Zircon Fission Track Thermochronology - Yuanlin Chen; Huan Li; Chaoyang Zheng; Safiyanu Muhammad Elatikpo; Liu’an Duan; Bo Feng; Dadou Li; Rehan Khan (Journal of Earth Science, 2023)

A three-dimensional active biochar for sintering in steel industry and remove methylene blue by synergistic activation of H3PO4 and ZnCl2 - Yu Zhang; Boxiong Shen; Muhammad Sajjad Ahmad; Wenjun Zhou; Rana Rehan Khalid; Muhammad Ibrahim; Awais Bokhari (Fuel, 2023)

A comprehensive review on phytochemistry, bioactivity and medicinal value of bioactive compounds of pomegranate (Punica granatum) - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Lufeng Wang; Shafeeqa Irfan; Muhammad Naeem Safdar; Mian Anjum Murtaza; Muhammad Nadeem; Shahid Mahmood; Ghulam Mueen-ud-Din; Hafiz Rehan Nadeem (Advances in Traditional Medicine, 2023)

Optimization of carboxylated graphene oxide (C-GO) content in polymer matrix: Synthesis, characterization, and application study - Zulfiqar Ahmad Rehan; Muhammad Zahid; Sidra Kanwal; Nimra Nadeem; Asif Hafeez; Asif Jamil; Zakariya Zubair (Chemosphere, 2023)

Polygeneration syngas and power from date palm waste steam gasification through an Aspen Plus process modeling - Arshid Mahmood Ali; Muhammad Shahbaz; Khurram Shahzad; Muddasser Inayat; Salman Naqvi; Abdulrahim Ahmad Al-Zahrani; Muhammad Imtiaz Rashid; Mohammad Rehan; Aishah Binti Mahpudz (Fuel, 2023)

Genome mining, antimicrobial and plant growth-promoting potentials of halotolerant Bacillus paralicheniformis ES-1 isolated from salt mine - Sajid Iqbal; Muhammad Qasim; Hazir Rahman; Naeem Khan; Rehan Zafar Paracha; Muhammad Faraz Bhatti; Aneela Javed; Hussnain Ahmed Janjua (Molecular Genetics and Genomics, 2023)

Exploring the mediating role of environmental strategy, green innovations, and transformational leadership: the impact of corporate social responsibility on environmental performance - Yasir Hussain; Kashif Abbass; Muhammad Usman; Muhammad Rehan; Muhammad Asif (Environmental Science and Pollution Research, 2022)

Performance evaluation and comparison of observed and reanalysis gridded precipitation datasets over Pakistan - Sayed Waseem Iqbal; Muhammad Latif; Rehan Ahmed; Shahzada Adnan; Muhammad Umar; Burhan Ahmad; Muhammad Azam; Jabir Hussain Syed (Theoretical and Applied Climatology, 2022)

Monitoring land use land cover changes and its impacts on land surface temperature over Mardan and Charsadda Districts, Khyber Pakhtunkhwa (KP), Pakistan - Rehan Khan; Huan Li; Muhammad Basir; Yuan Lin Chen; Meer Muhammad Sajjad; Ihtisham Ul Haq; Barkat Ullah; Muhammad Arif; Waqas Hassan (Environmental Monitoring and Assessment, 2022)

Applications of Biotechnology in Food and Agriculture: a Mini-Review - Muhammad Modassar Ali Nawaz Ranjha; Bakhtawar Shafique; Waseem Khalid; Hafiz Rehan Nadeem; Ghulam Mueen-ud-Din; Muhammad Zubair Khalid (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2022)

Staged energy and water quality optimization for large water distribution systems - Muhammad Nadeem Sharif; Ezzeddin Bakhtavar; Husnain Haider; Guangji Hu; Kasun Hewage; Rehan Sadiq (Environmental Monitoring and Assessment, 2022)

Climatology of dust storm frequency and its association with temperature and precipitation patterns over Pakistan - Mehwish Aziz Dar; Rehan Ahmed; Muhammad Latif; Muhammad Azam (Natural Hazards, 2022)

Spatio-temporal variability of drought characteristics across Pakistan - Jae Eun Lee; Muhammad Azam; Saif Ur Rehman; Muhammad Waseem; M. Naveed Anjum; Arslan Afzal; M. J. M. Cheema; Muhammad Mehtab; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Abid Sarwar; et al. (Paddy and Water Environment, 2022)

Convective available potential energy (CAPE) in Pakistan and its association with precipitation and temperature - Sameen Malik; Rehan Ahmed; Muhammad Latif; Muhammad Azam; Ehsan Haroon; Muhammad Bilal Iqbal (Theoretical and Applied Climatology, 2021)

Molecular detection and prevalence of Theileria ovis and Anaplasma marginale in sheep blood samples collected from Layyah district in Punjab, Pakistan - Kainat Abid; Sundas Bukhari; Muhammad Asif; Ayesha Sattar; Maryam Arshad; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Tropical Animal Health and Production, 2021)

Entomophagy: an innovative nutritional and economic navigational tool in race of food security - Rimsha Naseem; Waqar Majeed; Naureen Rana; Elmo Borges de Azevedo Koch; Muhammad Rehan Naseem (International Journal of Tropical Insect Science, 2021)

Mechanism and role of seeded native grasses to immobilize nitrogen on harvested blanket peat forests for protection of water courses - Zaki-ul-Zaman Asam; Connie O’Driscoll; Mohsin Abbas; Mark O’Connor; Muhammad Waqas; Mohammad Rehan; Abdul-Sattar Nizami; Liwen Xiao (Environmental Science and Pollution Research, 2021)

RLP, a bacteriophage of the family Podoviridae, rescues mice from bacteremia caused by multi-drug-resistant Pseudomonas aeruginosa - Iqbal Ahmad Alvi; Muhammad Asif; Rabia Tabassum; Rehan Aslam; Zaigham Abbas; Shafiq ur Rehman (Archives of Virology, 2020)

Approaches in Enhancing Thermotolerance in Plants: An Updated Review - Shafaqat Ali; Muhammad Rizwan; Muhammad Saleem Arif; Rehan Ahmad; Mirza Hasanuzzaman; Basharat Ali; Afzal Hussain (Journal of Plant Growth Regulation, 2020)

First Report Regarding the Simultaneous Molecular Detection of Anaplasma marginale and Theileria annulata in Equine Blood Samples Collected from Southern Punjab in Pakistan - Muhammad Asif; Asia Parveen; Sehrish Ashraf; Mureed Hussain; Munir Aktas; Sezayi Ozubek; Rehan Sadiq Shaikh; Furhan Iqbal (Acta Parasitologica, 2020)

Glycinebetaine alleviates the chromium toxicity in Brassica oleracea L. by suppressing oxidative stress and modulating the plant morphology and photosynthetic attributes - Rehan Ahmad; Shafaqat Ali; Muhammad Abid; Muhammad Rizwan; Basharat Ali; Asif Tanveer; Irfan Ahmad; Muhammad Azam; Muhammad Awais Ghani (Environmental Science and Pollution Research, 2020)

Spatiotemporal trends in reference evapotranspiration over South Korea - Ju Ha Hwang; Muhammad Azam; Maeng Seung Jin; Yong Ho Kang; Jae Eun Lee; Muhammad Latif; Rehan Ahmed; Muhammad Umar; Muhammad Zaffar Hashmi (Paddy and Water Environment, 2020)

Comparative effect of mesquite biochar, farmyard manure, and chemical fertilizers on soil fertility and growth of onion (Allium cepa L.) - Mumtaz Khan; Kaneez Fatima; Rehan Ahmad; Rafia Younas; Muhammad Rizwan; Muhammad Azam; Zain ul Abadin; Shafaqat Ali (Arabian Journal of Geosciences, 2019)

Thunderstorm frequency distribution and associated convective mechanisms over Pakistan - Rehan Ahmed; Muhammad Latif; Shahzada Adnan; Muhammad Khubaib Abuzar (Theoretical and Applied Climatology, 2019)

N-(2-hydroxyphenyl)acetamide and its gold nanoparticle conjugation prevent glycerol-induced acute kidney injury by attenuating inflammation and oxidative injury in mice - Rehan Ahmed Siddiqui; Shabana Usman Simjee; Nurul Kabir; Muhammad Ateeq; M. Raza Shah; Syed Saad Hussain (Molecular and Cellular Biochemistry, 2019)

Sugarcane waste straw biochar and its effects on calcareous soil and agronomic traits of okra - Muhammad Riaz; Mumtaz Khan; Shafaqat Ali; Muhammad Daud Khan; Rehan Ahmad; Muhammad Jamil Khan; Muhammad Rizwan (Arabian Journal of Geosciences, 2018)

Erratum to: Experimental investigation of immiscible supercritical carbon dioxide foam rheology for improved oil recovery - Shehzad Ahmed; Khaled Abdalla Elraies; Jalal Foroozesh; Siti Rohaida Bt Mohd Shafian; Muhammad Rehan Hashmet; Ivy Chai Ching Hsia; Abdullah Almansour (Journal of Earth Science, 2017)

Experimental investigation of immiscible supercritical carbon dioxide foam rheology for improved oil recovery - Shehzad Ahmed; Khaled Abdalla Elraies; Jalal Forooozesh; Siti Rohaida Bt Mohd Shafian; Muhammad Rehan Hashmet; Ivy Chai Ching Hsia; Abdullah Almansour (Journal of Earth Science, 2017)

Risk-based framework for optimizing residual chlorine in large water distribution systems - Muhammad Nadeem Sharif; Ashraf Farahat; Husnain Haider; Muhammad A. Al-Zahrani; Manuel J. Rodriguez; Rehan Sadiq (Environmental Monitoring and Assessment, 2017)

Promotive role of 5-aminolevulinic acid on chromium-induced morphological, photosynthetic, and oxidative changes in cauliflower (Brassica oleracea botrytis L.) - Rehan Ahmad; Shafaqat Ali; Fakhir Hannan; Muhammad Rizwan; Muhammad Iqbal; Zaidul Hassan; Nudrat Aisha Akram; Saliha Maqbool; Farhat Abbas (Environmental Science and Pollution Research, 2017)

Optimization of chlorination boosters in drinking water distribution network for Al-Khobar City in Saudi Arabia - Muhammad Nadeem Sharif; Ashraf Farahat; Muhammad A. Al-Zahrani; Nilufar Islam; Manuel J. Rodriguez; Rehan Sadiq (Arabian Journal of Geosciences, 2016)

Sources of Arsenic and Fluoride in Highly Contaminated Soils Causing Groundwater Contamination in Punjab, Pakistan - Abida Farooqi; Harue Masuda; Rehan Siddiqui; Muhammad Naseem (Archives of Environmental Contamination and Toxicology, 2009)